A new meshless method of solving 2D fractional diffusion-wave equations. (August 2022) - Du, Hong; Chen, Zhong
Abstract: In this paper, our important contributions are to provide the key of theories that the set of polynomial functions is dense in C 2 ( Ω ) . Based on the theories, we propose the block meshless method and use it to solve 2D variable-order FDWE on arbitrary domain. Numerical experiments further demonstrate advantages of the method. Highlights: We provide the key of theories that the set of polynomial functions is dense in C 2 ( Ω ) . We propose the block meshless method and use it to solve 2D variable-order FDWE on arbitrary domain. The proposed method use polynomial functions as basis functions and it can avoid complex computations of shape functions for traditional methods.